Pengaruh Financial Self Efficacy, Perilaku Keuangan, Keterampilan Wirausaha dan Financial Technology Terhadap Kinerja Keuangan UMKM - Rochmawati, Putri; Mawardi, M. Cholid; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to determine the influence of financial self efficacy, financial behavior, entrepreneurial skills and financial technology on the financial performance of MSMEs. Through a quantitative approach, data will be collected from MSMEs in Malang City. The results of this research are: 1) financial self efficacy has a significant effect on the financial performance of MSMEs, 2) financial behavior has a significant effect on the financial performance of MSMEs, 3) entrepreneurial skills have a significant effect on the financial performance of MSMEs, 4) financial technology has a significant effect on financial performance MSMEsKeywords: MSME financial performance, financial self efficacy, financial behavior, entrepreneurial skills and financial technology